2010
DOI: 10.1111/j.1440-1827.2010.02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of succinate dehydrogenase subunit B gene alterations in gastric cancers

Abstract: Recently, the succinate dehydrogenase subunit B gene, SDHB, has emerged as a novel tumor suppressor. In this study, we have examined the genetic and epigenetic alterations of the SDHB gene in sporadic gastric adenocarcinomas in order to investigate if the SDHB gene is involved in gastric carcinogenesis. The expression of SDHB proteins was also examined with immunohistochemistry and Western blot in 184 and eight gastric cancers, respectively. There was loss or reduced expression of SDHB in 45 (24.5%) of the 184… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Levels of SDHB are significantly decreased in human colon cancer tissues, and this is associated with tumor cell dedifferentiation 25 . SDHB showed reduced or loss of expression in 24.5% of gastric cancers but was not associated with clinical parameters, such as tumor invasion and differentiation 27 . A recent study also revealed decreased SDHB expression (48%) in HCC 28 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Levels of SDHB are significantly decreased in human colon cancer tissues, and this is associated with tumor cell dedifferentiation 25 . SDHB showed reduced or loss of expression in 24.5% of gastric cancers but was not associated with clinical parameters, such as tumor invasion and differentiation 27 . A recent study also revealed decreased SDHB expression (48%) in HCC 28 .…”
Section: Discussionmentioning
confidence: 87%
“…Germline mutations of SDHB were also associated with renal cell carcinoma, but not always with different morphologies 24 . SDHB expression has also been investigated in other general solid tumors, such as colon, gastric and breast cancers 25 27 . Levels of SDHB are significantly decreased in human colon cancer tissues, and this is associated with tumor cell dedifferentiation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that aberrant H3K27me3 regulation in immortal and tumorigenic cells is a consequence of altered energy metabolism in those cells. Many cancers have increased glycolysis and reduced tricarboxylic acid (TCA) cycle activity (30)(31)(32), which can lead to accumulation of succinate that in turn inhibits the H3K27 demethylase JMJD3 (33). Additionally, impaired TCA cycle use might result in reduced conversion of isocitrate to α-ketoglutarate, potentially limiting activities of H3K27 demethylases requiring this cofactor (34).…”
Section: Discussionmentioning
confidence: 99%
“…Defective OXPHOS may be driven by mutations in genes encoding its components. Mutations in nuclear genes encoding subunits of succinate dehydrogenase or proteins involved in assembling OXPHOS complex II are associated with hereditary cancers (Ricketts et al, 2012;Cao et al, 2010). Also alterations in the mitochondria-encoded OXPHOS genes are associated with invasive properties in human cancer cell lines.…”
Section: Changes In Oxidative Phosphorylation In Pre-cancerous Lesionmentioning
confidence: 99%